The Efficacy of the Mobile Library Service Program on Car Free Day as a Mechanism for Cultivating Reading Interest Among the Residents of Sragen - Safitri, Shofiya Nur; Riady, Yasir (Librarianship in Muslim Societies, 2025)
This research is motivated by innovations from libraries that provide mobile library services which aim to analyze the use of mobile library services at  the Car Free Day (CFD) event as a means to foster public interest in reading. The mobile library service present at Car Free Day (CFD) is expected to facilitate access to literacy and attention of the public, especially children and adolescents. This research uses a qualitative approach, where this research seeks to find detailed and in-depth information about a phenomenon or actual condition. The data collection techniques used are direct observation and interviews with officers and visitors to the mobile library. The results of the study show that the mobile library on Car Free Day (CFD) is able to attract people's interest in reading, with the majority of visitors coming from the age group of children and adolescents. The collection of books in demand includes children's storybooks and popular novel books. However, there are several obstacles such as limited book collections and unavailability of lending services. This study concludes that the mobile library on Car Free Day (CFD) has the potential to attract people's interest in reading, especially children. To increase its sustainability, it is recommended to add a variety of book collections and provide lending services